Influencia de las unidades de fotopolimerización sobre la microfiltración en resina bulk. revisión bibliográfica - Quilligana Salazar, Darnely Geordana (2024)
The use of composite resins has transformed the way dental treatments are performed by offering an esthetic and functional alternative to replace damaged or lost tooth structure. Despite their advantages, composite resins are not free of problems, and microleakage is one of the most common. The aim: Determine the influence of light-curing units on microleakage in bulk resin by means of a review of the literature. Materials and methods: For this purpose, a thorough search and analysis, such as PubMed, ScienceDirect and LILACS. The literature selection process will comprise clear and specific criteria, ensuring the inclusion of studies that provide relevant and updated information on microfiltration in BULK resin and light-curing units. Results Forty-four articles were initially collected, but after a selection process based on inclusion and exclusion criteria, 10 relevant articles were incorporated following PRISMA parameters. Conclusion: The results showed a wide variety of findings regarding the influence of light-curing units on microleakage in BULK resin, which underlines the complexity of the subject and the need for further research to obtain clearer and more definitive conclusions in this field.